THE STUDENTS' PERCEPTION ON THE USE OF ONLINE PLATFORM IN STUDYING ENGLISH - Hendi Septian Majid; Muh Syafei; Rusiana Rusiana (Prominent, 2022)
This research aimed to know the perception of fifth semester students of English Education Department of Universitas Muria Kudus on the use of online platform in Learning English and to find out what kinds of social media do the fifth semester students of English Education Department of Universitas Muria Kudus to learn English.